Determination of energy requirement for maintenance of adult non-lactating crossbred cows - GHOSH, A; MURARILAL, MURARILAL; HAQUE, N; KHAN, M Y (The Indian Journal of Animal Sciences, 2014)
Adult, non-lactating, non-pregnant, crossbred cows (6; 1/2 Holstein-Friesian x 1/2 Hariana), 7-to 8-year-old, weighing 334 to 438 kg, were divided into 2 groups of3 animals in each and fed at 2 different levels of feeding. The animals in both the groups were fed on isonitrogenous diets having 100 and 80% of metabolizable energy (ME) requirement in groups 1 (OE) and 2 (LE) respectively. Energy balance was determined in both the groups in open circuit respiration chamber in phase 1. In phase 2. animals in both the groups were interchanged and balance studies were repeated. Fasting heat production was determined individually in all the animals at the end of the experiment. The dry-matter intake was 73. 7±0.86 and 63.7±0.65 g/kg W0.75/day in OE and that in LE groups, respectively. The dry matter intake in OE group was significantly (P<0.01) higher than that in LE group. The digestibility of all the nutrients except ether extract was similar in both the groups. Nitrogen balance in all the animals was positive. Metabolizable energy intakes were 561.1±4.85 and 485.3±8.74 kJ/kg W0.75/day in OE and LE groups, respectively, which were significantly (P<0.05) different from each other. The energy balance was significantly (P<0.01) higher in OE group (+81.6±5.69) than that of LE group (+18.4±6.02 kJ/kg W0.75/day). The average value for fasting heat production of crossbred cows were 336.7 kJ/kg W0.75/day and ME requirement for maintenance determined to be 458.9 kJ/kg W0.75/day with an effiCiency of utilization (km) of 0.734.